Peningkatan Kapasitas Masyarakat Pesisir Terhadap Perubahan Iklim dan Adaptasinya: Coastal Communities Capacity Building Regarding Climate Change and its Adaptation - Fitriani, Vivi; La Gandri; Lies Indriyani; Abdul Manan; Kahirun; Sahindomi Bana; La Ode Midi (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2023)
Climate change has become a central issue in various sectors of life. Shifts at the start of the season, height changes, and rainfall variability have also been observed in several areas. A trend has also been found to increase the frequency and intensity of extreme climate events recently. Rising sea levels due to rising temperatures have caused increasing salinity problems and robs in various coastal areas of Indonesia. Currently, the beaches in the coastal area of Soropia District are used for multiple land use activities to support local community income. The impact of climate change accompanied by changes in environmental conditions in the coastal area of Tapulaga Village, Konawe Regency, requires special attention regarding the importance of disaster mitigation and adaptation efforts, which must be carried out collectively to create an ecologically resilient and adaptive village to climate change and ensure sustainable development in the area. Increasing the capacity of coastal communities to increase coastal communities' knowledge of climate change, increasing community participation and capacity, especially vulnerable groups affected by adverse disasters on the coast of Tapulaga Village. Through a participatory approach, the implementation of this activity shows a positive impact on community knowledge about climate change and its results, as well as building awareness of coastal communities to protect and preserve the environment, especially mangrove ecosystems, sustainably to prevent disasters due to climate change in the present and future.